EFFECTS OF COMPREHENSIBLE INPUT ON LANGUAGE ACQUISITION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This paper examines the role of comprehensible input in second language acquisition (SLA), supporting Krashen's Comprehension Hypothesis that language is acquired through meaningful input. Compared to traditional form-focused instruction (FFI), meaning-focused instruction (MFI) significantly improves vocabulary retention and practical language use. Studies show that visual aids, storytelling, and reading activities enhance natural language development, making comprehensible input essential for effective language teaching.